(untitled) (Colombia Medica, 2006)
The pathogenic protozoa Cryptosporidium sp. and Giardia sp. showed their infectivity and negative effects on the health of thousands of people in both developed and developing countries. Protozoa have ambient resistant stages that permit survived to physical and chemical treatment of drinking water. This risk is mainly related to the consumption of water whose microbiological quality indicators typically fulfill with current standards (fecal coliforms and Escherichia coli). Likewise, the discovery of new pathogens is calling for the development of new microbiological quality indicators that allow the production of really safe goods and services such as water for human consumption. Herein the authors present a literature review showing the impact of this microbiological risk in different populations.